Contrastive Analysis of Indonesian and Sundanese Verbs in SundaneseIndonesian Bilingual Children's Speech - Anisa Isnaeni Faturohmah; Baety, Annisa Nur; Rosidin, Odien (LPPM Universitas Dhyana Pura, 2025)
This study aims to analyze the differences and similarities of verbs in Indonesian and Sundanese as used by Sundanese Indonesian bilingual children. This research is motivated by the phenomenon of alternating use of two languages by children in daily community activities. In this study, a qualitative descriptive method was applied through an observational approach through the techniques of listening, seeing, engaged, and taking notes. From the results of the study, it can be seen that children tend to use Indonesian verbs in formal contexts such as at school, while Sundanese verbs are more dominant in family or local community interactions. There were also morphological differences, such as in the basic form and affix, as well as the phenomenon of code mixing and code switching in their speech. These findings suggest that language choice is influenced by social context and emotional proximity. This research is important for the preservation of regional languages and the development of bilingual teaching materials that are relevant to the socio-linguistic environment of children.